Level of motor performance in children in transition II with presence and absence of physical education teacher. (Revista horizonte, 2013)
The objective of this research is to identify, through the application of a circuit, the level of motor performance of children in transition II with the presence and absence of a Physical Education Teacher (PEF) at the Monteverde and Alemania kindergartens in the city of Temuco. Methods: The type of research contemplates a quasi-experimental, exploratory-descriptive, cross-sectional, quasi-experimental design, with a mixed approach. The sample was selected under a non-probabilistic criterion, by convenience that included 12 subjects, distributed in 5 females and 6 males, who are in the range of 5 years of age. Results: The results indicate that children with the presence of PEF achieve a higher frequency of compliance (66.7%) in most of the tests compared to subjects who do not have this professional (33.3%). Another striking aspect corresponds to the lowest motor performance, which belongs to a subject from the Kindergarten without PEF, who completed 21 of the 55 items that make up the circuit; while the subject with the best motor performance is part of the Kindergarten with the presence of PEF, who completed 52 items, which suggests a familiarization with this type of work. Conclusion: Finally, differences are observed in the motor performance of children in transition II with the presence and absence of PEF; however, these results are not essentially attributable to the presence of this professional.